Further Knowledge for Teachers and Children Practice English More: Teaching English for Young Learners - Asti Gumartifa; Dita Adawiyah (English Language in Focus (ELIF), 2023)
It is commonly recognized by informed teachers and educators that the discipline of children's English practice gains from a synthesis of applied linguistics, education psychology, and pedagogical perspectives. Young English language learners differ from adult English language learners in several learning practice. This would necessitate teacher consideration, on how to instruct students appropriately and effectively in the classroom. Studying English shouldn't be a stressful experience for children. At the age of the children category is the initial age to determine whether or not to like and dislike English. Teacher must provide teaching English with enjoyable. Therefore, activities of reading, listening, and speaking of English should become natural and easy for students as a result of their studies. Therefore, students can develop English with fun. This paper investigates some overviews of teaching English to young learners, such as; the importance of understanding among some student’s differences ages category, means of young learner, young learner’s characteristics, method of teaching young learner, and advantages and disadvantages in implementing TPR method. This study outlines several resources for EFL teachers to help children in learning a foreign language.